2017
DOI: 10.3389/fnbeh.2017.00022
|View full text |Cite
|
Sign up to set email alerts
|

Western Diet Chow Consumption in Rats Induces Striatal Neuronal Activation While Reducing Dopamine Levels without Affecting Spatial Memory in the Radial Arm Maze

Abstract: Rats fed high fat diets have been shown to be impaired in hippocampal-dependent behavioral tasks, such as spatial recognition in the Y-maze and reference memory in the Morris water maze (MWM). It is clear from previous studies, however, that motivation and reward factor into the memory deficits associated with obesity and high-fat diet consumption, and that the prefrontal cortex and striatum and neurotransmitter dopamine play important roles in cognitive performance. In this series of studies we extend our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 59 publications
3
12
0
Order By: Relevance
“…Animal models for obesity were developed by feeding rodents a semi-purified diet for several weeks with a fat content of more than 40% energy based on animal fats and the rodents developed obesity, hyperglycaemia, hypertriglyceridemia, and hyperleptinemia mimicking the pathophysiology of human obesity and metabolic syndrome [9,16,17]. Hence, diet-induced obesity models have become one of the most frequently used in studying obesity with high fat and cafeteria diets often employed in rats which have exhibited evidence of the role of over nutrition in energy homeostasis, body weight regulation, and adiposity [18][19][20][21]. e cafeteria diet consists of highly energetic and highly palatable human foods along with chow diet to trigger diet-induced obesity in laboratory rodents [22].…”
Section: Introductionmentioning
confidence: 99%
“…Animal models for obesity were developed by feeding rodents a semi-purified diet for several weeks with a fat content of more than 40% energy based on animal fats and the rodents developed obesity, hyperglycaemia, hypertriglyceridemia, and hyperleptinemia mimicking the pathophysiology of human obesity and metabolic syndrome [9,16,17]. Hence, diet-induced obesity models have become one of the most frequently used in studying obesity with high fat and cafeteria diets often employed in rats which have exhibited evidence of the role of over nutrition in energy homeostasis, body weight regulation, and adiposity [18][19][20][21]. e cafeteria diet consists of highly energetic and highly palatable human foods along with chow diet to trigger diet-induced obesity in laboratory rodents [22].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, diet induced obesity models are one of the most frequently used model for studying obesity (Giles, Jackman & MacLean, 2016). Diet-induced obesity models, including high-fat diets and cafeteria diets, have been employed to study obesity in rats (Crew, Waddell & Mark, 2016; Nguyen et al, 2017; Xia et al, 2018). These models have exhibited evidence of the role of overnutrition in energy homeostasis, body weight regulation and adiposity but there is a paucity of data regarding their nutritional composition (Hariri & Thibault, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Defects in the dopamine system lead to Parkinson's disease (PD), and Huntington's disease [ 12 14 ]. Recent study reported the correlation of dopamine with obesity [ 15 16 ]. Dopamine D2-receptor knockout in striatum increased compulsive eating and access to palatable food [ 16 ].…”
Section: Introductionmentioning
confidence: 99%